IMPACT OF INNOVATION AND TECHNOLOGICAL DEVELOPMENT ON REGINAL INDUSTRIAL POTENTIAL - Barchuk , V.P.; Sus, T.Yo. (The actual problems of regional economy development, 2016)
Abstract. In the article the analysis of the factors of region competitiveness, which is based on the innovative development strategy, is conducted. The objectives and priorities of the innovation and industrial activity development in the region are considered. It is proposed to use the principle of grouping of industrial production in the region according to the modernity of used technologies. It is noted that increasing of the competitiveness of Ukrainian industry and the defense ability of the country is possible only through the development of innovation activity both in the civilian and military spheres. The important factor is setting priorities in the most favored regime and financial support for the development of science intensive and high-tech productions that will allow modernizing and increasing of the industrial potential of the region. The main problem of innovative development of enterprises is the insufficient qualification of staff and lack of high tech industrial complex. JEL: R 58